Evaluation of medication package inserts in Iran - Shahriyar Shahbazi Khamas; Atefeh Jafari; Morvarid Zarif-Yeganeh; Hamidreza Taghvaye-Masoumi (Wolters Kluwer Medknow Publications, 2019)
Objective: Package inserts (PIs) provide information for the safe and effective use of medication. There is no study on the evaluation of PIs in Iran. The purpose of this study was to evaluate the completeness of PIs supplied with the 100 top-selling medications in Iran. Methods: This cross-sectional observational study was conducted during 3 weeks in January 2017. One hundred medications were chosen from a list supplied by the Iran Food and Drug Administration (IFDA). The PIs were assessed for the presentation and completeness of quality criteria, which was consisted of two parts. The first part was the criteria required by the IFDA, mentioned in Chapter 16 of the Pharmaceutical Regulations and Instructions provided by the IFDA. The second part of the criteria was defined according to the critical comments of clinical and industrial pharmacists. Findings: Thirty-seven out of 100 medications included no PIs. None of the PIs met all the criteria required by the IFDA. The highest score for completeness was 18 out of 21 (85.7%). Medication name, description, and adverse reaction were mentioned in all PIs. Other items such as patient counseling information (98%), warnings (95.2%), precautions (95.2%), pregnancy/lactation (95%), and storage condition (90.5%) have been mentioned in a high percentage of PIs. Conclusion: PIs have improved in recent years in Iran, but there is an absolute need for more accurate and up-to-date information. The IFDA should supervise pharmaceutical companies more strictly in this regard and should revise its regulations requiring PIs to conform to the FDA regulations.